Preoperative Serum Gamma-Glutamyltransferase as a Prognostic Biomarker in Patients Undergoing Radical Cystectomy for Bladder Cancer - Su, Shiqiang; Liu, Lizhe; Sun, Chao; Nie, Yanhua; Guo, Hong; Hu, Yang; Guo, Shunli; Pang, Shujian (Frontiers in Oncology, 2021)
Background Serum gamma-glutamyltransferase (GGT) has been reported to be correlated with survival in a variety of malignancies. However, its effect on patients with bladder cancer (BC) treated by radical cystectomy has never been evaluated. Patients and Methods We retrospectively evaluated 263 patients who underwent radical surgery in our center. Baseline features, hematologic variables, and follow-up data were obtained. The endpoints included overall survival (OS), cancer-specific survival (CSS), and disease-free survival (DFS). The relationship between GGT and survival were evaluated. Results The median follow-up period for all patients was 34.7 (22.9-45.9) months. At the last follow-up, 67 patients died, 51 patients died of cancer, 92 patients experienced disease recurrence. Patients with an elevated serum GGT had a higher rate of pT3-T4 tumors. Patients with a higher preoperative serum GGT had a lower rate of OS, CSS and DFS (P < 0.001 for all). Multivariate analysis identified that preoperative serum GGT was independent predictor of OS (HR: 3.027, 95% CI: 1.716-5.338; P < 0.001), CSS (HR: 2.115, 95% CI: 1.093-4.090; P = 0.026), DFS (HR: 2.584, 95% CI: 1.569-4.255; P < 0.001). Age, diabetes history, pathologic T stage, and lymph node status also were independent predictors of prognosis for BC patients. Conclusions Our results indicated that preoperative serum GGT was an independent prognosis predictor for survival of BC patients after radical cystectomy, and can be included in the prognostic models.